Wearable Radar System Design on Semi-Flexible PCB for Visually Impaired People - Zhang, Haoran; Yang, Yiming; Zhou, Jiahao; Shamim, Atif (Frontiers in Communications and Networks, 2022)
This paper presents a compact and wearable frequency-modulated continuous-wave (FMCW) radar on a semi-flexible printed circuit board (PCB) for an anti-collision system. This can enable visually impaired people to perceive their environment better and more safely in their everyday lives. In the proposed design, a multiple-input multiple-output (MIMO) antenna array with four receivers (RXs) and three transmitters (TXs) has been designed to achieve obstacle-detection ability in both horizontal and vertical planes through a specific geometrical configuration. Operating at 76–81 GHz, an aperture coupled wide-beam patch antenna with two parasitic patches is proposed for each channel of RXs and TXs. The fast Fourier transform (FFT) algorithm has been implemented in the radar chip AWR1843 for intermediate frequency (IF) signals to generate a range-Doppler map and search precise target angles in high sensitivity. The complete system, which includes both the MIMO antenna array and the radar chip circuit, is utilized on a six-layer semi-flexible PCB to ensure compactness and ease in wearability. Field testing of the complete system has been performed, and an obstacle-detection range of 7 m (for humans) and 19 m (for larger objects) has been obtained. A wide angular detection range of 64-degree broadside view (± 32°) has also been achieved. A voice module has also been integrated to deliver the obstacle’s range and angle information to visually impaired persons.